Mechano-growth factor E-domain modulates cardiac contractile function through 14-3-3 protein interactomes - Solís, Christopher; Thompson, Walter C.; Peña, James R.; McDermott-Roe, Christopher; Langa, Paulina; Warren, Chad M.; Chrzanowska, Magdalena; Wolska, Beata M.; Solaro, R. John; Pieter Detombe,; Goldspink, Paul H. (Frontiers in Physiology, 2022)
In the heart, alternative splicing of the igf-I gene produces two isoforms: IGF-IEa and IGF-IEc, (Mechano-growth factor, MGF). The sequence divergence between their E-domain regions suggests differential isoform function. To define the biological actions of MGF’s E-domain, we performed in silico analysis of the unique C-terminal sequence and identified a phosphorylation consensus site residing within a putative 14-3-3 binding motif. To test the functional significance of Ser 18 phosphorylation, phospho-mimetic (S/E18) and phospho-null (S/A18) peptides were delivered to mice at different doses for 2 weeks. Cardiovascular function was measured using echocardiography and a pressure-volume catheter. At the lowest (2.25mg/kg/day) and highest (9mg/kg/day) doses, the peptides produced a depression in systolic and diastolic parameters. However, at 4.5mg/kg/day the peptides produced opposing effects on cardiac function. Fractional shortening analysis also showed a similar trend, but with no significant change in cardiac geometry. Microarray analysis discovered 21 genes (FDR P<0.01), that were expressed accordant with the opposing effects on contractile function at 4.5mg/kg/day, with the nuclear receptor subfamily 4 group A member 2 (Nr4a2) identified as a potential target of peptide regulation. Testing the regulation of the Nr4a family, showed the E-domain peptides modulate Nr4a gene expression following membrane depolarization with KCl in vitro. To determine the potential role of 14-3-3 proteins, we examined 14-3-3 isoform expression and distribution. 14-3-3γ localized to the myofilaments in neonatal cardiac myocytes, the cardiac myocytes and myofilament extracts from the adult heart. Thermal shift analysis of recombinant 14-3-3γ protein showed the S/A18 peptide destabilized 14-3-3γ folding. Also, the S/A18 peptide significantly inhibited 14-3-3γ’s ability to interact with myosin binding protein C (MYPC3) and phospholamban (PLN) in heart lysates from dobutamine injected mice. Conversely, the S/E18 peptide showed no effect on 14-3-3γ stability, did not inhibit 14-3-3γ's interaction with PLN but did inhibit the interaction with MYPC3. Replacing the glutamic acid with a phosphate group on Ser 18 (pSer18), significantly increased 14-3-3γ protein stability. We conclude that the state of Ser 18 phosphorylation within the 14-3-3 binding motif of MGF’s E-domain, modulates protein-protein interactions within the 14-3-3γ interactome, which includes proteins involved in the regulation of contractile function.